ANALISIS FAKTOR DETERMINASI KINERJA KARYAWAN PADA PABRIK AIR MINUM DALAM KEMASAN HEXAHAQ TENGGALEK - Ifadatin, Putri (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Hexahaq Trenggalek Packaged Drinking Water Factory is an industry in the field of drinking water supply. Early research was conducted in order to determine the HR in the Hexahaq Trenggalek Bottled Drinking Water Factory, especially on the performance of factory employees. Leadership, work ethic and work environment are important aspects that will be examined at the Hexahaq Trenggalek Bottled Water Factory. These three variables have a major influence on the factory so that further research needs to be done. The population is 40 employees of Hexahaq Trenggalek Bottled Water Factory by using questionnaires as data collection. All of these three variables obtained significant values, which means that all variables have an influence on the performance of Hexahaq Trenggalek Bottled Drinking Water Factory employees. The results of the analysis state that all variables have a large impact on performance. By 69.8% these three variables affect the performance of the Hexahaq Trenggalek Bottled Drinking Water Factory. It is hoped that with this research the performance system at the Hexahaq Trenggalek Bottled Drinking Water Factory will increase.